2022
DOI: 10.2495/sdp220271
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study and Comparative Efficiency of Islamic Geometric Patterns as a Retrofit Strategy in Mid-Rise Buildings of Al Ain City, Abu Dhabi, Uae

Abstract: The city of Al Ain (Abu Dhabi, UAE) has a significant amount of mixed-use mid-rise buildings, especially in the city's central district. Because of the harsh arid climate of Al Ain, many of these buildings have high energy demands to accommodate the cooling load. By taking inspiration from the traditional Islamic architectural element, Mashrabiya, this study is concerned with exploring and identifying various, optimal Islamic geometric pattern (IGP) configurations used in cladding systems, with respect to ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Mohammadi et al [18] study analyzed IGPs in Persian architecture to be able to apply complex and irregular patterns to meet the modern design requirements in generating new patterns or recreating traditional designs. The most recent 2022 had in total four publications; two were about the effective role of IGPs in achieving significant reductions in energy consumption (i.e., [19,20]), and two about the aesthetic phenomenology of Islamic geometry within the context of interior design [21] and use of computational aided technology to classify IGPs [5].…”
Section: Application Of Igps In the Modern Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Mohammadi et al [18] study analyzed IGPs in Persian architecture to be able to apply complex and irregular patterns to meet the modern design requirements in generating new patterns or recreating traditional designs. The most recent 2022 had in total four publications; two were about the effective role of IGPs in achieving significant reductions in energy consumption (i.e., [19,20]), and two about the aesthetic phenomenology of Islamic geometry within the context of interior design [21] and use of computational aided technology to classify IGPs [5].…”
Section: Application Of Igps In the Modern Designmentioning
confidence: 99%
“…It is observed that the dominant aspect is the combination of environmental and economic aspects of sustainability. This is because of the use of computeraided technologies and computational methods to either perform analysis or develop new The most recent 2022 had in total four publications; two were about the effective role of IGPs in achieving significant reductions in energy consumption (i.e., [19,20]), and two about the aesthetic phenomenology of Islamic geometry within the context of interior design [21] and use of computational aided technology to classify IGPs [5].…”
Section: Sustainability Involvement In Islamic Geometric Patterns (Igps)mentioning
confidence: 99%
See 1 more Smart Citation